Evaluasi Program Pekarangan Pangan Lestari (P2L) dengan Model Context, Input, Process dan Product (CIPP) di Kecamatan Matesih, Kabupaten Karanganyar - Musthofa, Muhammad Safrudin; Sugihardjo, Sugihardjo; Permatasari, Putri (Fakultas Pertanian Universitas Jember, 2023)
The Sustainable Food Yard Program is a program that focuses on the utilization of fruit and vegetable cultivation in yards. One of the implementations is the Lismatu Bhakti Women Farmer Group, the Ngudi Barokah Farmer Group, and the Sumber Gede Farmer Cadets Group. All three groups are in Matesih District, Karanganyar Regency. However, in its implementation, there are various obstacles, such as the allocation of funds in the middle of the year, low group participation, the fact that the group is not yet solid, and the lack of an evaluation from PPL or the local office. This study used a qualitative descriptive method with purposive sampling of informants and snowball sampling. The evaluation model used is context, input, process, and product (CIPP). The data collection process was obtained from Forum Group Discussion (FGD), in-depth interviews, participatory observation, and documents. Data validity was determined through source and method triangulation. The results of the study obtained three (3) evaluation criteria, namely fulfilled, not fulfilled, and not fulfilled based on the 2021 P2L technical guidelines. It was found that the context aspect was not fulfilled because the group was not yet solid and member participation was low, while the input and process aspects had been fulfilled because they were in accordance with the directives of the technical guidelines and there were funds of Rp. 50,000,000 that were used for the four main activities of the P2L program. Furthermore, the product aspect has not been fulfilled because the P2L program has not had a significant impact on groups or the community.